Mission Impossible: Afghan Peace Talks. - Pasoon, Ali Ahmad. (Tufts Archival Research Center, 2017)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: In this paper it is argued, that contrary to the popular belief among politicians and analysts of Afghanistan's affairs, the Afghan conflict in its present stage is simply too complex to be resolved through peaceful means and peace talks with the Taliban. The fact is that the calls for peace talks with Taliban are inspired not by genuine belief and rational calculations that the talks would bring peace to Afghanistan but by desperation and disillusionment with military operations against Taliban which have yielded little strategic success since the insurgency began. The reality is that not only Taliban have no interest in peace talks in the current conditions but there are too many state and non-state actors with diverging interests and agendas involved in this conflict that satisfying the demands of all parties through a peace deal with the Taliban is impossible.